2016
DOI: 10.1097/dcr.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

National Early Rectal Cancer Treatment Revisited

Abstract: Transanal endoscopic microsurgery had comparable 5-year relative survival to total mesorectal excision in T1 rectal cancer but inferior 5-year relative survival in T2 rectal cancer. Transanal endoscopic microsurgery was associated with higher local recurrence rates for both T1 and T2 tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 25 publications
0
41
0
3
Order By: Relevance
“…Some studies have found no difference between local excision and TME surgery in local recurrence rates or outcomes of patients with T1 rectal cancer [7, 14, 29]. However, Stornes et al [6] studied 543 patients with T1 rectal cancer and reported that the local recurrence rate was 14.5% in patients who underwent transanal endoscopic microsurgery, which was significantly higher than the recurrence rate (1.4%) in patients who underwent TME ( p < 0.001). The 5-year OS rate was significantly lower in the transanal endoscopic microsurgery group (65.3%) than in the TME group (81.5%, p = 0.012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have found no difference between local excision and TME surgery in local recurrence rates or outcomes of patients with T1 rectal cancer [7, 14, 29]. However, Stornes et al [6] studied 543 patients with T1 rectal cancer and reported that the local recurrence rate was 14.5% in patients who underwent transanal endoscopic microsurgery, which was significantly higher than the recurrence rate (1.4%) in patients who underwent TME ( p < 0.001). The 5-year OS rate was significantly lower in the transanal endoscopic microsurgery group (65.3%) than in the TME group (81.5%, p = 0.012).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of local recurrence after local excision ranges from 11 to 18% [6-8, 10, 12-14, 26, 27]. In rectal cancer, 27% of metastatic lymph nodes were reported to be 3 mm or less in diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Registry studies show that fertility-sparing versus radical surgery for stage I ovarian cancer result in excellent (98%) 5-year survival rates in both groups, albeit with fewer recurrences in the former groups [47]. Optimal management of early-stage tumors is an area of debate where the registries have provided relevant data on favorable results in early-stage renal cell cancer and the use of transanal endoscopic microsurgery in T1 rectal cancer [28,48]. Clinical registry data can also be applied to build prediction models based on complex clinical information such as consultations, imaging, biomarkers and tumor data, to define patient groups that can be spared adjuvant treatment or need of intensified surveillance and/or rehabilitation [49][50][51][52][53][54][55].…”
Section: Monitoring Changing Principles Of Carementioning
confidence: 99%
“…Although there were not differences in distant metastases rates and overall survival, a higher risk of local recurrence was evidenced [9, 10]. Similarly, data from Norwegian Colorectal Cancer Registry show the absence of differences in 5-year relative survival rate but a significant lower 5-year local recurrence rate after total mesorectal excision [11]. …”
Section: Management Of Local Diseasementioning
confidence: 99%